Chalkony a jejich heterocyklické analogy jako potenciální terapeutika bakteriálních onemocnĕní - Opletalová, V (Ceska a Slovenska farmacie, 2000)
Chalcones and their heterocyclic analogues possess a number of biological effects. Their antifungal effects were reported in the previous communication (Opletalová V., Sedivý D.: Ces. a Slov. Farm. 48, 252 (1999)). The present review is devoted to the antibacterial activity of these compounds. For antibacterial activity, the presence of the enone aggregate in the molecule is important. Hydrogenated analogues are less effective or ineffective, saturated brominated analogues are effective probably after a metabolic transformation into unsaturated alpha-bromochalcone. In the rings, substitution with a hydroxyl is advantageous, in some cases also substitution with a lipophilic substituent, e.g. a halogen or an alkyl, proved to be advantageous. On the other hand, substitution with amino groups often results in a decrease in effectiveness. Effectiveness of chalcones and their derivatives against gram-positive microorganisms is usually higher than against gram-negative bacteria. Some analogues, however, inhibited also the growth of gram-negative strains. With regard to increased incidence of tuberculosis in recent years, antimycobacterial effectiveness of chalcones and their derivatives is especially interesting.
Keywords: Bacterial Infections; vztahy mezi strukturou a aktivitou; Molecular Structure; Humans; Structure-Activity Relationship; molekulární struktura; lidé; bakteriální infekce; Chalcone; antibakteriální látky; Anti-Bacterial Agents; chalkon